The Influence of Principal Professional Competence on the Quality of Elementary School Education - Nunung Kurnia Retnowati; Widya Kusumaningsih; I Made Sudana (Lembaran Ilmu Kependidikan, 2025)
The quality of education is the ability of the education system to manage and process education in a quality and effective manner to increase added value in order to produce quality output. The quality of education is a problem that is considered by the Indonesian government. Quality or quality in the field of education includes the quality of input, process, and output or outcome. Input quality is the quality that is seen from various inputs for the learning process to occur, including curriculum, facilities, students and various other things that contribute to the learning process. While the quality of the process is the quality that is seen from the extent to which students feel comfortable with the learning services carried out by teachers with various resources owned by the school. While the quality of the results is the quality of the results of education that are felt especially by students as a real manifestation of the learning process. The low quality of education in Randublatung District can also be seen from the output of the quality of education on student achievement in various competitions. In managing school resources, the principal does not do it transparently and accountably.There are several factors that influence the improvement of education quality, including: (a) Educational objective factors; (b) Educational input factors; (c) Educational management and supervision factors; (d) Educational personnel factors (students, teachers, staff, principals, supervisors); (e) Educational facilities and infrastructure factors (curriculum, facilities, equipment, learning, buildings, workshops, libraries and others); (f) Institutional factors (all parties related to the implementation of education); (g) Science, technology, and art factors learned by students. Using a quantitative and ex post facto correlational research approach, this study involved 207 Dabin II teachers, Randublatung District, Blora Regency, as many as 207 teachers from 26 elementary schools and a sample of 136 teachers was taken. Data were collected through questionnaires and analyzed using validity, reliability, normality, linearity, multicollinearity, and heteroscedasticity tests. Based on the results of data processing using the SPSS version 22 for Windows program, the highest score was 128, the lowest score was 59, the average (mean) was 95.04; median 96.00; and standard deviation of 18.814. From the table and graph above, it is known that the results of the questionnaire on the professional competence of school principals show that 21 people (15.44%) are in the bad category, 26 people (19.12%) are in the less good category, 31 people (22.79%) are in the fairly good category, 33 people (24.26%) are in the good category, and 25 people (18.38%) are in the very good category. The average (mean) of the principal's professional competence variable data is 95.04. The mean value is in the class interval 87 - 100 so that it is in the "Quite Good" category.